Instructional Design of Flipped Classroom using Prob-lem Posing Strategy for English Class in Grade V of Elementary Student - Nuril Amini; Tuti Iriani; Iva Sarifah (Green Publisher Indonesia, 2025)
English instruction at the elementary level often struggles with fostering engagement and critical thinking among students. This research aims to address these challenges by developing an instructional design that combines the flipped classroom model with a problem-posing strategy for fifth-grade English learners. The research adopts the Dick and Carey development model, supported by Leung’s problem-posing framework, to create a structured learning approach grounded in constructivist and critical pedagogy theories. Data were collected through classroom observations, interviews, pre- and post-tests, and expert validations. The design was evaluated by learning, media, and material experts with high feasibility ratings of 89%, 86%, and 88%, respectively. Implementation of the model in a classroom setting demonstrated substantial improvements in student outcomes, with critical thinking scores rising from 48% to 93% and English comprehension improving from 70% to 88%. Statistical analysis confirmed the effectiveness of the model (p < 0.05). These findings underscore the model's ability to enhance student engagement, critical thinking, and language proficiency. The research contributes to pedagogical innovation by extending flipped learning and problem-posing strategies to younger learners, suggesting their broader applicability in early education. It also provides practical insights for educators and curriculum developers seeking to implement interactive and student-centered instructional models in the digital age.